The Dynamic Crust of Northern Afar and Adjacent Rift Margins: New Evidence From Receiver Function Analysis in Eritrea and Ethiopia - M. Gauntlett; S. N. Stephenson; J.‐M. Kendall; C. Ogden; J. O. S. Hammond; T. Hudson; B. Goitom; G. Ogubazghi (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Afar is undergoing the final stages of continental rifting and hosts the triple junction between the Red Sea, Gulf of Aden, and Main Ethiopian rifts. To better understand the nature of the crust and continental breakup in the region, we calculate teleseismic receiver functions across northeastern Afar and the Danakil microplate, using new data from a regional deployment in Eritrea. We estimate the Moho depth and bulk crustal VP/VS ratio using the H‐κ stacking method. The heterogeneity of our crustal thickness estimates (∼19–35 km) indicates that the Danakil microplate has undergone stretching and crustal thinning. By investigating the relationship between crustal thickness and topographic elevation, we estimate the regional crustal bulk density as ρc ≈ 2,850 ± 20 kg m−3, which is higher than expected, given the crustal thickness of the region. We show that topography is 1.5 ± 0.4 km higher than would be expected due to crustal isostasy alone. We propose that this topography is supported by the same hot mantle upwelling suggested to be responsible for the onset of rifting in East Africa. Uplift is generated due to the presence of a hot thermal anomaly beneath the plate and by thinning of the lithospheric mantle. Our results are consistent with a number of independent constraints on the thermal structure of the asthenospheric and lithospheric mantle. Evidence of melt within the crust is provided by anomalously high VP/VS ratios of >1.9, demonstrating that magma‐assisted extension continues to be important in the final stages of continental breakup.